Broadleaved trees enhance biodiversity of the understorey vegetation in boreal forests - Salemaa, Maija; Hotanen, Juha-Pekka; Oksanen, Jari; Tonteri, Tiina; Merila, Paivi (Elsevier Scientific Publ. Co, 2024)
Understorey vegetation constitutes a remarkable part of the total biodiversity of boreal forests. Mixing broadleaved trees in coniferous forests has been shown to enhance vascular plant abundance and species richness, while high stand density has a counteracting effect. However, more information is needed on how environmental factors modify these biodiversity responses.We investigated how the proportion of broadleaved trees of total basal area, tree species richness, stand density, and shrub cover were reflected in the number of vascular plant species and percentage cover of herbs and bilberry (Vaccinium myrtillus). We also studied the response of site fertility indicators, i.e. C:N ratio and extractable calcium concentration in the soil organic layer, to broadleaved species in mixed-forests.The study was based on the data of understorey vegetation, soil, and stand properties in forests on mineral soil, inventoried on a systematic sample plot network in Finland in 2006. We used a subset of 307 plots in the hemi-southern and middle boreal zones and divided the plots either to xeric or mesic types. We used generalized additive models in analysing the data.Birches (Betula sp.) were the main broadleaved species. Vascular species richness and herb cover generally increased with increasing proportions of broadleaved trees and tree species number both on mesic and xeric sites but decreased with increasing stand density on mesic sites. An increase in proportion of broadleaved trees and stand density resulted in decreased bilberry cover in the southern boreal zone, probably due to stand shading, but in increased cover in the middle boreal zone. Vegetation responses to increasing shrub cover often showed unimodal shape. As increase of proportion of broadleaved trees correlated positively with calcium and negatively with C:N of the organic layer, we suggest that nutrient input from easily decomposable birch leaf litter promotes species richness and herb cover via improved nutrient availability in the soil.Our results ...